2022
DOI: 10.1371/journal.pone.0269655
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging improvement in HPV vaccination coverage among adolescent girls in Kampala, Uganda

Abstract: Introduction WHO recommends vaccination against HPV for girls before sexual debut. Uganda started HPV vaccination in 2008 as pilot programs in 2 districts, followed by national roll out in 2015. Despite the availability of vaccines against human papillomavirus (HPV) in Uganda in the period covered by the study, there was reported low HPV vaccine uptake and completion especially of the second dose in Uganda; with little information available on timely completion of HPV vaccine and the associated factors in Ugan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(41 reference statements)
0
6
1
Order By: Relevance
“…The high uptake of the HPV vaccine reported in these countries could have been because the survey was conducted immediately after an HPV vaccine demonstration project involving mass immunization of young girls in school and communities through campaign programs which was not the case for this current survey. Additionally, the uptake of the HPV vaccine in this current study was lower than that reported by a study conducted in Central Uganda (43.3%) [ 15 ]. The difference in the findings could be due to the fact that this study was conducted in an adolescent clinic setting whereas our study was a community-based survey.…”
Section: Discussioncontrasting
confidence: 85%
“…The high uptake of the HPV vaccine reported in these countries could have been because the survey was conducted immediately after an HPV vaccine demonstration project involving mass immunization of young girls in school and communities through campaign programs which was not the case for this current survey. Additionally, the uptake of the HPV vaccine in this current study was lower than that reported by a study conducted in Central Uganda (43.3%) [ 15 ]. The difference in the findings could be due to the fact that this study was conducted in an adolescent clinic setting whereas our study was a community-based survey.…”
Section: Discussioncontrasting
confidence: 85%
“…Consequently, it implies that individuals in the youngest age bracket exhibit the highest inclination and readiness to receive the vaccine, despite potentially possessing less experience and knowledge compared to young adults or parents. Given the characteristics of young adolescents, it becomes imperative to provide them with support in the critical thinking process to effectively absorb and discern information pertaining to cervical cancer and the HPV vaccine (Lismidiati et al, 2022;Patrick et al, 2022). By doing so, their understanding and self-efficacy can be further refined, subsequently enhancing their attitudes and intentions regarding vaccine acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Among adolescents, a study conducted in Uganda revealed that only 43.3% of girls achieved timely completion for both doses of the HPV vaccination, which reflected their lack of self-efficacy (Patrick et al, 2022). Conversely, a study in Indonesia examined self-efficacy in adolescents regarding HPV vaccine uptake (Lismidiati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…HPV vaccine is usually delivered in Uganda via school-based outreach programmes [18]. Although schools remained closed throughout 2020, the MOH supplied a specific grant to support HPV vaccine delivery through community outreach, integrated with child health days, later in 2020 (pers.…”
Section: Plos Onementioning
confidence: 99%